Positive allosteric modulators that target NMDA receptors rectify loss-of-function GRIN variants associated with neurological and neuropsychiatric disorders. (15th October 2020) - Tang, Weiting; Liu, Ding; Traynelis, Stephen F.; Yuan, Hongjie
Abstract: N -methyl-d -aspartate receptors (NMDARs) mediate a slow component of excitatory synaptic transmission that plays important roles in normal brain function and development. A large number of disease-associated variants in the GRIN gene family encoding NMDAR GluN subunits have been identified in patients with various neurological and neuropsychiatric disorders. Many of these variants reduce the function of NMDARs by a range of different mechanisms, including reduced glutamate potency, reduced glycine potency, accelerated deactivation time course, decreased surface expression, and/or reduced open probability. We have evaluated whether three positive allosteric modulators of NMDAR receptor function (24( S )-hydroxycholesterol, pregnenolone sulfate, tobramycin) and three co-agonists (d -serine, l -serine, and d -cycloserine) can mitigate the diminished function of NMDARs harboring GRIN variants. We examined the effects of these modulators on NMDARs that contained 21 different loss-of-function variants in GRIN1, GRIN2A, or GRIN2B, identified in patients with epilepsy, intellectual disability, autism, and/or movement disorders. For all variants, some aspect of the reduced function was partially restored. Moreover, some variants showed enhanced sensitivity to positive allosteric modulators compared to wild type receptors. These results raise the possibility that enhancement of NMDAR function by positive allosteric modulators may be a useful therapeutic strategy. Highlights: Effects of PAMs and co-agonists on disease-associated GRIN variants were evaluated. PAMs can enhance function of NMDARs harboring loss-of-function GRIN variants. Co-agonists can augment glycine to enhance NMDAR function. Enhancement of NMDAR function by PAMs may be a useful therapeutic strategy.